Evaluation of in vitro and in vivo anticancer potential of two 5-acetamido chalcones against breast cancer - Wankhede, Sonal; Kumar, Nitesh; Simon, Lalitha; Biswas, Subhankar; Gourishetti, Karthik; Ramalingayya, Grandhi Venkata; Joshi, Mit; Rao, C. Mallikarjuna (Technische Universität Dortmund, 2017)
Two 5’acetamido chalcones, C1 and C2 were synthesized by Claisen-Schmidt condensation method and characterized by IR, LC-MS, 1H NMR and 13C NMR. These compounds were evaluated for anticancer activity in vitro in breast cancer cell lines (MCF-7 and MDA-MB-231) using MTT assay, anti-metastatic assay, apoptotic screening by AO/EB staining and in vivo in N-Methyl-N-nitrosourea (MNU) induced breast carcinoma model. Sprague-Dawley rats with developed tumors (50 mg/kg MNU i.p.) were grouped in four, namely MNU control (0.25 % of CMC p.o.), standard group (doxorubicin 2 mg/kg once in 4 days, i.p.), C1 and C2 groups (50 mg/kg p.o. each). After 21 days of treatments, tumor volume and weight were assessed. Excised tumors were subjected to DNA fragmentation study. MTT assay showed IC50 values of 62.56 and 37.8 µM by for C1 and C2. Both compounds increased apoptotic bodies more than 3 fold compared to normal control in AO/EB staining. Antimeta- static (scratch wound) assay showed a significant (p<0.05) reduction in cell migration after 24 h and 48 h treat- ments compared to normal control. In in vivo studies, tumor weight and tumor volume were significantly (p<0.05) reduced in the doxorubicin group as well as in test groups compared to MNU control. DNA fragmentation assay showed an increase in the number of bands formed in C1 and C2 compared to normal control. Results obtained from in vitro and in vivo studies demonstrated the significant anticancer potentials of C1 and C2.
EXCLI Journal;Vol. 16 2017
Keywords: Chalcones; Breast cancer; N-methyl-N-nitrosourea; 610